2017
DOI: 10.1111/gcb.13963
|View full text |Cite
|
Sign up to set email alerts
|

Warming‐induced upward migration of the alpine treeline in the Changbai Mountains, northeast China

Abstract: Treeline responses to environmental changes describe an important phenomenon in global change research. Often conflicting results and generally too short observations are, however, still challenging our understanding of climate-induced treeline dynamics. Here, we use a state-of-the-art dendroecological approach to reconstruct long-term changes in the position of the alpine treeline in relation to air temperature at two sides in the Changbai Mountains in northeast China. Over the past 160 years, the treeline in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
51
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 69 publications
2
51
2
3
Order By: Relevance
“…Recent photographic comparisons have shown that climate change during the past several decades has caused glacier retreat and subsequent upward shifts of the alpine tree line in the area (Baker & Moseley, ). This is in line with findings for the wider Asian mountain region, where there is widespread evidence for climate‐related glacier shrinkage and tree and shrub line advancement (Cogley, ; Du et al, ; Myers‐Smith & Hik, ), potentially threatening regional endemism in alpine communities.…”
Section: Introductionsupporting
confidence: 88%
“…Recent photographic comparisons have shown that climate change during the past several decades has caused glacier retreat and subsequent upward shifts of the alpine tree line in the area (Baker & Moseley, ). This is in line with findings for the wider Asian mountain region, where there is widespread evidence for climate‐related glacier shrinkage and tree and shrub line advancement (Cogley, ; Du et al, ; Myers‐Smith & Hik, ), potentially threatening regional endemism in alpine communities.…”
Section: Introductionsupporting
confidence: 88%
“…The growth limitation hypothesis states that tree growth at treelines is primarily controlled by temperature during the growing season (Holtmeier & Broll, ; Körner, ), so climatic warming should enhance growth and favor an upslope shift of alpine treelines. Warmer conditions have been associated with increased tree regeneration and encroachment at treeline ecotones worldwide (Camarero & Gutiérrez, ; Liang et al, ; Liang, Wang, Eckstein, & Luo, ), and also with upward treeline shifts in many sites (Beckage et al, ; Du et al, ; Harsch et al, ; Huang et al, ; Peñuelas, Ogaya, Boada, & Jump, ). Changes in the patterns of distributional limits of tree species at treelines, however, are not homogenous and depend on many local‐scale interactions (Camarero et al, ; Case & Duncan, ; Elliott, ; Kharuk, Ranson, Im, & Vdovin, ; Liu & Yin, ; Loranger, Zotz, & Bader, ; Wang, Camarero, Luo, & Liang, ; Wang, Liang, Sigdel, Liu, & Camarero, ; Zhu, Woodall, & Clark, ).…”
Section: Introductionmentioning
confidence: 99%
“…This leads to adaptive changes in the species and physiological characteristics of the trees. Many studies have shown that low temperature is the main limiting factor for alpine treeline formation and can explain nearly 80% of the global variability of alpine treeline elevation [3,4,14]. Non-structural carbohydrates (NSC), including soluble sugars and starch, are critical energy involved in plant growth and metabolism [15][16][17].…”
mentioning
confidence: 99%
“…[27], while the highest distribution of the evergreen conifer Picea jezoensis is 1800 m a.s.l. With climate warming, the upper limit of their distribution may shift up to varying degrees [3]. Thus, understanding the physiological adaptation of different treeline species to environmental changes enables more effective predictions of the alpine treeline and tree species distribution shifts in the future.In this study, we selected P. jezoensis and B. ermanii, the treeline species naturally occurred in Changbai Mountain, and measured the concentration of NSC, soluble sugars and starch in one-year-old leaves, shoots, stems and fine roots along with elevation.…”
mentioning
confidence: 99%